Complete-arch accuracy of seven intraoral scanners measured by the virtual-fit method - Borbola, Daniel; Mikolicz, Akos; Romanszky, Laszlo; Sersli, Gyorgy; DeFee, Michael; Renne, Walter; Vag, Janos (Journal of dentistry, 2024)
This study compared the accuracy of seven intraoral scanners (IOS) by the virtual-fit method. Four maxillary arches with tooth abutments were scanned with an industrial reference scanner (n=1) and by Aoralscan3, EmeraldS, Helios600, Lumina, Mediti700, Primescan, and Trios5 IOSs (each n=12). Two complete-arch fixed frameworks were designed on each IOS scan with a 70 µm (group 70) and a 90 µm internal cement space (group 70+20, additional 20 µm at the margin). The virtual-fit method was comprised of superimposing the framework designs onto the reference scan using a non-penetrating algorithm simulating the clinical try-in. Internal and marginal gaps were measured. Precision was estimated by the mean absolute errors (MAE). In group 70, Mediti700 (43 µm), Primescan (42 µm), and EmeraldS were in the best homogenous subset for the marginal gap, followed by the Lumina (67 µm), Aoralscan3 (70 µm), and Trios5 (70 µm), whereas Helios600 (118 µm) was in the third subset. Based on the MAE at the margin, Mediti700, Trios5, and EmeraldS were in the first-best homogenous subset, followed by Primescan. Lumina and Helios600 were in the third subset, and Aoralscan3 was in the fourth subset. In group 70+20, the marginal gap was significantly decreased for Lumina and Aoralscan3, whereas MAE significantly decreased for EmeraldS and Aoralscan3. The rank of IOSs was similar for the internal gap. EmeraldS, Mediti700, Primescan, and Trios5 meet the marginal and internal fit criteria for fixed tooth-borne complete arch restorations. Increasing the cement space during design could enhance restoration fit. The virtual-fit alignment method can effectively evaluate the accuracy of different intraoral scanners, offering valuable clinical guidance for distinguishing among them. Recent software and hardware versions of long-standing IOS manufacturers are suitable for fabricating complete arch restoration.